Body composition and behaviour in adult rats are influenced by maternal diet, maternal age and high-fat feeding. (4th February 2015) - Ware, S.; Voigt, J.-P.; Langley-Evans, S. C.
Abstract: Fetal exposure to maternal undernutrition has lifelong consequences for physiological and metabolic function. Maternal low-protein diet is associated with an age-related phenotype in rats, characterised by a period of resistance to development of obesity in early adulthood, giving way to an obesity-prone, insulin-resistant state in later adulthood. Offspring of rats fed a control (18 % casein) or low-protein (9 % casein; LP) diet in pregnancy were challenged with a high-fat diet at 9 months of age. To assess whether other maternal factors modulated the programming effects of nutrition, offspring were studied from young (2–4 months old) and older (6–9 months old) mothers. Weight gain with a high-fat diet was attenuated in male offspring of older mothers fed LP (interaction of maternal age and diet; P  = 0·011) and adipose tissue deposition was lower with LP feeding in both males and females ( P  < 0·05). Although the resistance to weight gain and adiposity was partially explained by lower energy intake in offspring of LP mothers ( P  < 0·001 males only), it was apparent that energy expenditure must be influenced by maternal diet and age. Assessment of locomotor activity indicated that energy expenditure associated with physical activity was unlikely to explain resistance to weight gain, but showed that offspring of older mothers were more anxious than those of younger mothers, with more rearing observed in a novel environment and on the elevated plus-maze. The data showed that in addition to maternal undernutrition, greater maternal age may influence development and long-term body composition in the rat.